2018
DOI: 10.4103/1793-5482.180894
|View full text |Cite
|
Sign up to set email alerts
|

Isolated intramedullary spinal cysticercosis: A case report with review of literature of a rare presentation

Abstract: A number of parasitic infections can involve the central nervous system of which neurocysticercosis (NCC) is the most common one in developing countries. Most often the brain is involved, spine and spinal cord involvement is very rare and intramedullary involvement is rarer still. Here, we report a 30-year-old male patient, with intramedullary NCC of dorsal spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The most common parasitic central nervous system involvement, neurocysticercosis (NCC) is caused by the larval form of a nematode, Taenia solium. [1,2] NCC is endemic in various low socio-economic countries like Africa, Mexico, Latin America and Asia, including India. [4,5] NCC is considered to be the most common cause of acquired epilepsy as 80% of cases present with seizures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The most common parasitic central nervous system involvement, neurocysticercosis (NCC) is caused by the larval form of a nematode, Taenia solium. [1,2] NCC is endemic in various low socio-economic countries like Africa, Mexico, Latin America and Asia, including India. [4,5] NCC is considered to be the most common cause of acquired epilepsy as 80% of cases present with seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Even though intracranial neurocysticercosis is a well known parasitic infestation of CNS worldwide, intraspinal involvement, and particularly intramedullary NCC, is extremely rare even in endemic areas despite being known to coexist with intracranial NCC. [1,4] George A Alsina et al (2002) in their study brought out less than 200 reported cases of spinal NCC worldwide even after including three fourth cases having an underlying/associated intracranial NCC. [9] It is postulated that approximately 100 fold blood supply of brain parenchyma as compared to spine is responsible for an increased incidence of intracranial NCC and intramedullary lesion results from direct hematogenous or ventriculo-ependymal spread.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations